An innovative U-shaped sludge bed anammox process for nitrogen removal. (15th November 2018) - Cui, Fenghao; Kim, Minkyung; Kim, Moonil
Abstract: In this study, we proposed an innovative U-shaped sludge bed reactor which could be a cost effective and simplified approach for the operation of an anammox reactor. The performance for nitrogen removal and the composition of bacterial communities were investigated for about 500 days of operation. The nitrogen removal rate could be approximately 85% when the total nitrogen loading rate was about 0.54 kg N/m 3 /d. The 16S rRNA gene pyrosequencing analysis of the bacterial community determined that Betaproteobacteria (class level) of the ammonia-oxidizing bacteria (AOB) community, Nitrospira (genus level) of the nitrite-oxidizing bacteria (NOB) community, and Brocadia (genus level) of the anammox bacteria community simultaneously coexisted in the reactor sludge. These results demonstrated that simultaneous growth and coexistence of AOB, NOB, and anammox were capable within the reactor. Furthermore, a mathematical modeling system was developed to simulate the nitrification and anammox processes. The model simulation showed that the oxygen was rapidly depleted and that led to a drop in the activity of AOB and NOB, then the growth of anammox bacteria started under anaerobic conditions. Highlights: A new operating type of bioreactor cultivated anammox bacteria in settled sludge. Effective nitrogen removal was demonstrated using cost effective reactor operation. The simultaneous presence of AOB, NOB, and anammox communities was determined. The Monod kinetic model showed interaction between anammox and nitrification. A simplified and effective anammox reactor operating strategy was advised.